Coalition government and party mandate: explaining ministerial room of manoeuvre vis-à-vis the coalition agreement - Moury,Catherine (2009)
In this article, I look at the dialectic between parties and government to understand the extent to which ministers are bound by the coalition agreement. I first observe that considering the coalition agreement as a contract written by the parties for the government to avoid “agency losses” is an oversimplification. In almost all cases the main ministers have participated in the negotiations, with, or as, party leaders. I also observe that the government follows to a large extent the coalition agreement in Belgium and in the Netherlands and also, although to a lesser extent in Italy, in where the coalition agreement are drafted before the elections. Moreover, if ministers have to fulfil the coalition agreement, they will do it better if they have participated in its draft. The transfer of the program only tells one part of the extent to which ministers are bound by the coalition agreement: measuring the proportion of ministerial decision based on the coalition agreement is also significant. The results of this measurement enlighten once more the importance of the coalition agreement for ministers, as at least one third (and up to two thirds) of the governmental bills originate in the coalition agreement. We observe much more variation on this second dimension and the crucial variable explaining a high proportion of agreement-based decisions is the absence of party leaders in the government. This finding suggests that party leaders will tend to accept more non agreement-based ministerial initiatives when they are themselves ministers.